2009
DOI: 10.1007/s11274-009-0277-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new EC formulation derived from garlic creeper (Adenocalymma alliaceum Miers.) against anthracnose and stem end rot diseases of mango

Abstract: Different leaf extracts of Garlic creeper (Adenocalymma alliaceum Miers.) using water and solvents were prepared and they were screened for their antifungal activity against Colletotricum gloeosporioides Penz. and Botryodiplodia theobromae Pat. causal agents of mango post harvest diseases viz., anthracnose and stem end rot respectively. Among the extracts tested, chloroform extract was found to be highly effective in inhibiting the spore germination of C. gloeosporioides by 84.62% and B. theobromae by 84.50% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, thyme essential oil has not been studied for use as an additive to fruit preservation due to its strong odor, thermal instability and low ash point. 56,57 These problems can be solved by embedding thyme essential oil with b-cyclodextrin.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…However, thyme essential oil has not been studied for use as an additive to fruit preservation due to its strong odor, thermal instability and low ash point. 56,57 These problems can be solved by embedding thyme essential oil with b-cyclodextrin.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The methanolic extract of garlic creeper at 2.5 and 10.0 per cent inhibited the growth of Pythium aphanidermatum and Macrophomina phaseolina respectively (Girijashankar and Thayumanavan, 2005). Chloroform extracts of the leaves of garlic creeper were highly effective in inhibiting the mycelial growth and spore germination of Colletotrichum gloeosporioides (anthracnose) and Botrytis theobromae (stem end rot) in mango (Aswini et al, 2010). They also reported that thin layer chromatography of the leaf extracts revealed the presence of phenolic compounds viz., tannic acid and resorcinol, which had antimicrobial activity by reacting on sulph hydryl groups of pathogen enzymes.…”
Section: Screening Of Botanicals For Biofumigation Potentialmentioning
confidence: 99%
“…Garlic powder is an herbal formulation used in ayurvedic system of medicine for the treatment of platelets aggregation: the interaction of garlic with heparin has been studied in influence to platelets aggregation effect of standard drug in various parameters. No sign toxicity was observed during toxicity study (5). The effects of garlic on the osmotic fragility of red blood cells in albino rats were assessed in vivo and in vitro.…”
Section: Herbal Antidandruff Shampoo Containing Garlicmentioning
confidence: 99%